2019
DOI: 10.1177/0036933019856567
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic seminoma with isolated gastric metastases: a case report

Abstract: Gastric metastases are a rare occurrence in patients with malignancy. In case reports of these arising from germ cell tumours, the majority were non-seminomatous germ cell tumours and had evidence of retroperitoneal involvement. We present a unique case of a 67-year-old man with metastatic testicular pure seminoma. He presented with dyspepsia and investigation found isolated metastases to the gastric mucosa and sub-mucosa from a right testicular primary. No lymph node involvement was identified. The patient wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…The first hypothesis suggests that metastases may occur via the lymph drainage duct to the testis and epididymis. Gastric metastases have also been reported to originate from testicular cancer, probably via invasion of the stomach by testicular cancer through lymphatic ducts[ 13 - 15 ]. It is reported that testicular and gastric cancers have overlapping lymphatic metastasis pathways[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first hypothesis suggests that metastases may occur via the lymph drainage duct to the testis and epididymis. Gastric metastases have also been reported to originate from testicular cancer, probably via invasion of the stomach by testicular cancer through lymphatic ducts[ 13 - 15 ]. It is reported that testicular and gastric cancers have overlapping lymphatic metastasis pathways[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our case, most germ cell tumors with gastric metastasis have a nonseminoma component [ 6 ]. There are few reported cases of pure seminoma presenting at diagnosis with gastric metastases, both with and without macroscopic retroperitoneal ganglia involvement [ 7 , 8 , 9 ]. Most of these cases report a single gastric metastasis and some are associated with other visceral organ metastases, unlike our patient.…”
Section: Discussion/conclusionmentioning
confidence: 99%